Retalho palatino para tratamento de fístula buco-sinusal - Macedo, Maicon Douglas Souza (2023)
Considering that the occurrence of oro-sinusal communications is a post-surgical complication that arises more frequently after the extraction of upper molars due to the anatomical proximity between the apices of dental roots and the maxillary sinus, the diagnosis of this complication requires clinical and radiographic procedures, with the Valsalva maneuver being a crucial step in the physical examination. If not treated properly, direct communication between the maxillary sinus and the oral cavity can result in the formation of permanent fistulas caused by the epithelialization of the mucosa. It is the responsibility of the dentist to choose the best treatment technique, considering the size of the defect, the anatomical area, and the time elapsed since its creation. The purpose of this work is to describe a clinical case of post-extraction oro- sinusal fistula that was not corrected early. The palatal flap technique was chosen as a favorable option to close the sinus defect while preserving keratinized mucosa and vestibular sulcus anatomy.